Ruang Publik Deliberatif Digital: Analisis Platform Symbolic ID dalam Perspektif Demokrasi Deliberatif Jürgen Habermas - Rizqian, Dimas Rahman (Jurnal Sosial Politik dan Hukum, 2025)
This article explores the application of Jürgen Habermas’s deliberative democracy in the digital platform Symbolic ID. By positioning “usefulness” as the primary interaction parameter, Symbolic ID aims to construct an inclusive and meaningful public sphere. This paper analyzes how metacognitive features and the “Insignia Social” component of the platform resonate with Habermas’s ideas of communicative rationality, public discourse, and active participation. The findings indicate that Symbolic ID represents a practical attempt to foster democratic digital deliberation amid the noise and polarization of online discourse.